MEMBANGUN PERADABAN YANG LEBIH ADIL - Kusumohamidjojo, Budiono (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2007)
The widespread misperception about identity has apparently led to identity absolutism that is also reflected in the quest for absolute truth. The consequence of this mindset has placed mankind in a “confederation of cultures” (Amartya Sen) that ultimately fails to deliver a peaceful and just coexistence. As if human suffering is yet to be hardened, globalization brought more burden into the drama. We are like destined to watch human civilization split into various conflicting civilizations. As mankind hasreached an unprecedented complex Lebenswelt (EdmundHusserl),we need to develop a kind of global civilization (to reconcile the effects of  globalization) that is more just in order for the human race to retain itsexistence and co-existence.Ways and means need to be determined for that purpose, however, argumentative dialogue still seems to be the main avenue to achieve that end. For its own sake Indonesia has the obligationto contribute to the development of a more just global civilization. Such obligation is indeed implied in the Preamble of its 1945 Constitution. Otherwise Indonesians risk to be at the mercy of arbitrary forces of globalization. Nevertheless, Indonesia's capacity to participate at and contribute to the process of developing a more just civilization depends very much on improvement of the qualities of its citizens, which in turn requires adjustment of mindset with the ongoing process. Efforts to adjust our mindset will need the rendering of subjects on social ethics (budi pekerti), world history and global geography starting with the elementary school. Only with reasoning citizens will Indonesia be able to participate in the development of a more just civilization and thereby also improve its ownwell being.